Pendidikan Pesantren Tradisional dalam Perspektif Pendidikan Modern - Wahid, Abdul; Ali Maftuh, Moh (Al Hikmah: Jurnal Studi Keislaman, 2023)
Abstract: Traditional Islamic boarding schools, that is, Islamic boarding schools that have not changed from their original form, only instruct texts published in Arabic in the 15th century by experts known as the Yellow Book. The curriculum is totally determined by the kiai who look after the Islamic boarding school and follows the halaqah system (deliberation), which is used in mosques or surau. Pesantren people have long utilized and benefited from traditional Islamic boarding school education. But in the modern era, advancement is happening very quickly throughout many industries, particularly in education. The evolution of the times themselves gave rise to modern education. where research is done to further education's improvement in the contemporary educational system. Keywords: Modern Education and Traditional Islamic Boarding Schools